KORELASI MOTIVASI DAN KECERDASAN EMOSIONAL DENGAN HASIL BELAJAR TEMATIK SISWA KELAS V SEKOLAH DASAR - Shafira Aprilia; Kartono Kartono; Siti Halidjah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis study aims to describe the level of correlation between motivation andemotional intelligence with student learning outcomes in thematic learning in classV Elementary School 36 South Pontianak. The method used in this research isdescriptive method with the form of correlation studies. This research is apopulation study with 49 students. Data collection techniques used in this study areindirect communication techniques and documentary study techniques. The toolsused to collect data were questionnaires and document student learning outcomes.The result of the research is that student motivation is 89.41% in the very goodcategory and 85.25% of the emotional intelligence of students is in the goodcategory and student learning outcomes get an average score of 79.28. Based onstatistical analysis using a multiple correlation formula to calculate the correlationbetween motivation and emotional intelligence with student learning outcomes, ther count is 0.081, and r table is 0.281, this means rcount <rtabel or (0.081 <0.281).The conclusion is the correlation between motivation and emotional intelligencewith student learning outcomes in thematic learning in class V Elementary School36 South Pontianak is included in the very low category.Keywords:Emotional Intelligence, Motivation, Learning Outcomes